2014
DOI: 10.1016/j.ajhg.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GTPBP3 Cause a Mitochondrial Translation Defect Associated with Hypertrophic Cardiomyopathy, Lactic Acidosis, and Encephalopathy

Abstract: Respiratory chain deficiencies exhibit a wide variety of clinical phenotypes resulting from defective mitochondrial energy production through oxidative phosphorylation. These defects can be caused by either mutations in the mtDNA or mutations in nuclear genes coding for mitochondrial proteins. The underlying pathomechanisms can affect numerous pathways involved in mitochondrial physiology. By whole-exome and candidate gene sequencing, we identified 11 individuals from 9 families carrying compound heterozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 30 publications
4
125
1
5
Order By: Relevance
“…When the mitochondrial release factor (mtRF1a) recognizes the stop codon and binds to the mitoribosome, mitochondrial translation termination is conducted [24]. Previous studies suggested inhibition or defects of mitochondrial translation were correlated to acute myeloid leukemia [25] and hypertrophic cardiomyopathy [26]. Meanwhile, dysregulations of mitochondria are usually correlated to multiple malignant diseases [27].…”
Section: Discussionmentioning
confidence: 99%
“…When the mitochondrial release factor (mtRF1a) recognizes the stop codon and binds to the mitoribosome, mitochondrial translation termination is conducted [24]. Previous studies suggested inhibition or defects of mitochondrial translation were correlated to acute myeloid leukemia [25] and hypertrophic cardiomyopathy [26]. Meanwhile, dysregulations of mitochondria are usually correlated to multiple malignant diseases [27].…”
Section: Discussionmentioning
confidence: 99%
“…Las mutaciones en GTPBP3 (OMIM*608536), identificadas por primera vez en 2014 entre una muestra de pacientes con mitocondriopatías, producen cardiomiopatía hipertrófica infantil y acidosis láctica, con un 50% de los casos en los que se asocia también con síntomas neurológicos (Kopajtich et al 2014). En los pacientes GTPBP3, los complejos I y IV del sistema OXPHOS presentan una actividad reducida respecto al control y en 3 de los 4 casos en los que se ha analizado la síntesis mitocondrial de proteínas se ha encontrado una disminución significativa.…”
Section: Mutaciones En Gtpbp3unclassified
“…En humanos, mutaciones en MTU1, MTO1 y GTPBP3 producen disfunción de la fosforilación oxidativa mitocondrial, debido a que afectan a la actividad y a los niveles estacionarios de los complejos OXPHOS, principalmente de los complejos I y IV (Zeharia et al 2009;Ghezzi et al 2012;Kopajtich et al 2014;Tischner et al 2015). Por homología con las proteínas humanas y debido a que MTTU-1, MTCU-1 y MTCU-2 modifican los tRNAs mitocondriales de C. elegans, en este trabajo se ha investigado el efecto de las mutaciones knockout de mttu-1, mtcu-1 y mtcu-2 en diversos aspectos de la fisiología mitocondrial.…”
Section: La Inactivación De Mttu-1 Mtcu-1 Y Mtcu-2 Provoca Disfuncióunclassified
See 2 more Smart Citations